Echo of worlds - Carey, M. R., 1959- (Carey, M. R., 1959- Pandominion, 2024)
Two mighty empires are at war - and both will lose, with thousands of planets falling to the extinction event called the Scour. At least that's what the artificial intelligence known as Rupshe believes. But somewhere in the multiverse there exists a force - the Mother Mass - that could end the war in an instant, and Rupshe has assembled a team to find it. Essien Nkanika, a soldier trying desperately to atone for past sins; the cat-woman Moon, a conscienceless killer; the digitally recorded mind of physicist Hadiz Tambuwal; Paz, an idealistic child and the renegade robot spy Dulcimer Coronal. Their mission will take them from the hellish prison world of Tsakom to the poisoned remains of a post-apocalyptic Earth, and finally bring them face to face with the Mother Mass itself. But can they persuade it to end eons of neutrality and help them? And is it too late to make a difference? Because the Pandominion's doomsday machines are about to be unleashed - and not even their builders know how to control them.